2023
DOI: 10.3390/bs13110913
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Physical Activity in People with Dementia: A Systematic Review and Narrative Synthesis

Ruth W. Feenstra,
Liese J. E. de Bruin,
Marieke J. G. van Heuvelen

Abstract: Physical activity (PA) has positive effects on the physical and cognitive functioning of people with dementia. Knowledge about what limits and stimulates people with dementia to participate in PA is essential to promote effective PA implementation and enhance PA levels. Previous reviews primarily included opinion-based studies, using data from interviews, focus groups or dyads. By including implementation studies, we aimed to elaborate on previous reviews by identifying new barriers to PA and new facilitators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Evidence from the literature demonstrated that dementia gradually impairs cognitive and behavioral functioning, which is the most important cause of care reliance [ 55 , 56 , 57 , 58 ]; therefore, patients with severe dementia require greater assistance from caregivers because of a lack of capacity to manage their physical and psychological needs. As explored in the study by Feenstra (2023), factors influencing PA in PLWD revealed potential barriers and facilitators; hence, addressing such problems is crucial in promoting physical activity and mitigating dependence [ 59 ]. Furthermore, engaging in exercise, as highlighted by Chen’s study, leads to better upper body strength, aerobic endurance, and balance in PLWD [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the literature demonstrated that dementia gradually impairs cognitive and behavioral functioning, which is the most important cause of care reliance [ 55 , 56 , 57 , 58 ]; therefore, patients with severe dementia require greater assistance from caregivers because of a lack of capacity to manage their physical and psychological needs. As explored in the study by Feenstra (2023), factors influencing PA in PLWD revealed potential barriers and facilitators; hence, addressing such problems is crucial in promoting physical activity and mitigating dependence [ 59 ]. Furthermore, engaging in exercise, as highlighted by Chen’s study, leads to better upper body strength, aerobic endurance, and balance in PLWD [ 60 ].…”
Section: Discussionmentioning
confidence: 99%